The Senate Reference: Constitutional Change and Democracy - Dawood, Yasmin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
The Senate Reference is ultimately a decision about how democratic decision making ought to be conducted when the role and function of fundamental democratic institutions are themselves at stake. This case stands for the idea that unilateral decision making by Parliament is not permitted even if from a substantive standpoint the government’s proposals are “more democratic” than the status quo. Consultative elections and senatorial term limits, for example, would arguably make the Senate a more representative and accountable body. Yet the Court held that such changes are subject to the Constitution’s general amending formula, which means that Parliament cannot implement these changes on its own. This article suggests that the Court’s interpretation of the amending procedures is based upon a deeper democratic commitment to ensuring dialogue and deliberation between and among the relevant stakeholders. The Court’s approach has benefits and drawbacks. By setting itself up as the exclusive arbiter of the Constitution’s “internal architecture” and the primary decision-maker as to what constitutes an institution’s “fundamental role and nature”, the Court has enhanced its own authority over the evolution of the constitutional order while significantly narrowing the possibilities for constitutional change. While the Court’s approach has the undeniable effect of making large-scale institutional reform difficult (if not impossible), the alternative is arguably worse. If it were possible for the government to unilaterally reform democratic institutions, then it could unilaterally reform them in an anti-democratic direction as well.